The effects of a green Rooibos (Aspalathus linearis) extract on metabolic parameters and adipose tissue biology in rats fed different obesogenic diets. Issue 24 (28th November 2022) - Kotzé-Hörstmann, L. M.; Bedada, D. T.; Johnson, R.; Mabasa, L.; Sadie-Van Gijsen, H.
Abstract : Supplementation with Rooibos extract modulated metabolic markers, adipocyte size and adipose stem cell (ASC) function in rats, under different dietary conditions. This is the first in vivo / ex vivo study to demonstrate effects of Rooibos on ASCs. Abstract : Current pharmaceutical treatments addressing obesity are plagued by high costs, low efficacy and adverse side effects. Natural extracts are popular alternatives, but evidence for their anti-obesity properties is scant. We assessed the efficacy of a green (minimally-oxidized) Rooibos ( Aspalathus linearis ) extract (GRT) to ameliorate the effects of obesogenic feeding in rats, by examining body weight, metabolic measures, adipose tissue cellularity and tissue-resident adipose stem cells (ASCs). Furthermore, we performed statistical correlations to explore the relationships and interactions between metabolic and adipose tissue measures. Using an in vivo / ex vivo study design, male Wistar rats were maintained for 17 weeks on one of 3 diets: CON (laboratory chow), OB1 (high-sugar, medium fat) or OB2 (high-fat, high-cholesterol) ( n = 24 each). From weeks 11–17, half of the animals in each group received oral GRT supplementation (60 mg per kg body weight daily). Blood and tissue samples were collected, and ASCs from each animal were cultured. Diets OB1 and OB2 induced divergent metabolic profiles compared to CON, but metabolic measures within dietary groups were mostly unaffected by GRT supplementation. Notably, diets OB1 and OB2 uncoupled the positive association between visceral adiposity and insulin resistance, while GRT uncoupled the positive association between elevated serum cholesterol and liver damage. Obesogenic feeding and GRT supplementation induced adipocyte enlargement in vivo, but lipid accumulation in cultured ASCs did not differ between dietary groups. Larger adipocyte size in subcutaneous fat was associated with favourable glucose metabolism measures in all GRT groups. In conclusion, GRT affected the associations between systemic, adipose tissue-level and cellular measures against the background of obesogenic diet-induced metabolic dysregulation.